Exome sequencing in Crisponi/cold‐induced sweating syndrome–like individuals reveals unpredicted alternative diagnoses. Issue 5 (28th March 2019) - Angius, Andrea; Uva, Paolo; Oppo, Manuela; Buers, Insa; Persico, Ivana; Onano, Stefano; Cuccuru, Gianmauro; Van Allen, Margot I.; Hulait, Gurdip; Aubertin, Gudrun; Muntoni, Francesco; Fry, Andrew E.; et al.
Abstract : Crisponi/cold‐induced sweating syndrome (CS/CISS) is a rare autosomal recessive disorder characterized by a complex phenotype (hyperthermia and feeding difficulties in the neonatal period, followed by scoliosis and paradoxical sweating induced by cold since early childhood) and a high neonatal lethality. CS/CISS is a genetically heterogeneous disorder caused by mutations in CRLF1 (CS/CISS1), CLCF1 (CS/CISS2) and KLHL7 (CS/CISS‐like). Here, a whole exome sequencing approach in individuals with CS/CISS‐like phenotype with unknown molecular defect revealed unpredicted alternative diagnoses. This approach identified putative pathogenic variations in NALCN, MAGEL2 and SCN2A . They were already found implicated in the pathogenesis of other syndromes, respectively the congenital contractures of the limbs and face, hypotonia, and developmental delay syndrome, the Schaaf‐Yang syndrome, and the early infantile epileptic encephalopathy‐11 syndrome. These results suggest a high neonatal phenotypic overlap among these disorders and will be very helpful for clinicians. Genetic analysis of these genes should be considered for those cases with a suspected CS/CISS during neonatal period who were tested as mutation negative in the known CS/CISS genes, because an expedited and corrected diagnosis can improve patient management and can provide a specific clinical follow‐up. Abstract : Genetic analysis of NALCN, MAGEL2 and SCN2A should be considered for those cases with a suspected Crisponi/cold‐induced sweating syndrome (CS/CISS) during neonatal period who were tested as mutation negative in the known CS/CISS genes, because an expedited and corrected diagnosis can improve patient management and can provide a specific clinical follow‐up.